Phentermine and topiramate for the management of obesity: a review - Cosentino G; Conrad AO; Uwaifo GI (Dove Medical Press, 2013)
Gina Cosentino,1 Ariane O Conrad,2 Gabriel I Uwaifo1 1Section of Endocrinology, Diabetes and Metabolism, Department of Medicine, Louisiana State University Health Sciences Center, New Orleans, LA, USA; 2Xavier University of Louisiana College of Pharmacy, New Orleans, LA, USA Abstract: Obesity is now a major public health concern worldwide with increasing prevalence and a growing list of comorbidities and complications. The morbidity, mortality and reduced productivity associated with obesity and its complications result in a major burden to health care costs. Obesity is a complex chronic medical syndrome often with multiple different etiologic factors in individual patients. The long term successful management of obesity remains particularly challenging and invariably requires a multifaceted approach including lifestyle and behavioral modification, increased physical activity, and adjunctive pharmacotherapy. Bariatric surgery remains a last resort though at present it has the best results for achieving sustained robust weight loss. Obesity pharmacotherapy has been very limited in its role for long term obesity management because of the past history of several failed agents as well as the fact that presently available agents are few, and generally utilized as monotherapy. The recent FDA approval of the fixed drug combination of phentermine and extended release topiramate (topiramate-ER) (trade name Qsymia™) marks the first FDA approved combination pharmacotherapeutic agent for obesity since the Phen-Fen combination of the 1990s. This review details the history and clinical trial basis for the use of both phentermine and topiramate in obesity therapeutics as well as the results of clinical trials of their combination for obesity treatment in humans. The initial clinical approval trials offer evidence that this fixed drug combination offers synergistic potential for effective, robust and sustained weight loss with mean weight loss of at least 10% of baseline achieved and sustained for up to 2 years in over 50% of subjects treated. It is anticipated that this agent will be the first in a new trend of multi-agent combination therapy for the chronic adjunctive management of obesity. Keywords: obesity, dysmetabolic syndrome, anorexiants, obesity pharmacotherapy, cardiovascular risk factors, obesity complications